PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR GO PUBLIK - Fadlikah, Umi; Zahro, Fatimatuz (Commodities, Journal of Economic and Business, 2022)
This study aims to determine the Influence of Capital Structure and Financial Performance on Company Values in Go Public Manufacturing Companies (Case Study of Food and Beverage Sector Listed on the Indonesia Stock Exchange for the 2014-2017 Period). This research is quantitative research. The population in this study were 18 companies. While the sample in this study were 10 companies. Data collection techniques arecarried out by non-participant observation techniques. The variables in this study are capital structure and financial performance as independent variables, and firm value as the dependent variable. The data used in this study are secondary data, literature and web searching. The data analysis technique used is panel data analysis. Based on the results of this study, it was found that there was no significant effect between capital structure on firm value. The results of the analysis show a significance of 0.918 or greater than 0.05 (p = 0.918> 0.05), which means that H0 is accepted. The effect of the capital structure on the value of the company is because the capital structure is not an investor's focus in stock purchase decisions at the company. While financial performance has a significant influence on company value. The results of the analysis show a significant amount of 0.003 or smaller than 0.05 (p = 0.003> 0.05), which means H1 is accepted. High financial performance will provide an indication of good corporate prospects so that it can trigger investors to participate in increasing stock demand. Increasing demand for shares will cause increased company value.